(untitled) (Journal of Contemporary Educational Policies and Practices, 2020)
This paper aims to adjust the concept of Total Quality Management (TQM) and make it fit for use in higher education institutes. The article describes the results of a design science research. Based on experiences in Egypt and the Netherlands, the characteristics of higher education are defined as well as the specifics of educational processes. These lead to a translation of TQM in educational terms. The experiences result in a model that can be used as framework to implement TQM in higher education institutes. The experiences that form the base for the design are limited to two countries with two different cultures. There is no evidence concerning the use of the model in any other country in the world. It is known that there have been many initiatives to implement TQM in higher education. The combination with quality management in teaching and learning models (Transformative Mode, An Engagement Model of Program Quality, University of Learning Model, A Model for a Responsive University) is scarce as well as application in two such different countries.